THE EFFECT OF THERAPEUTIC COMMUNICATION ON PATIENT SATISFACTION OF THE HALODOC TELEMEDICINE APPLICATION - Mutiah Mutiah; Firda Tri Widyarakhma (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2022)
This study aims to see if there is an effect of therapeutic communication through the media carried out by doctors on the Halodoc telemedicine application on patient satisfaction using the application. The approach used in this study is a quantitative approach with a survey method conducted by distributing questionnaires to one hundred respondents according to predetermined criteria, namely users of the Halodoc telemedicine application aged 18 to 25 years, residing in Bojonegoro, East Java and using the feature chat with doctors during the COVID-19 pandemic. The results of this study are: 1. Therapeutic communication with media performed by doctors has a significant effect on patient satisfaction using the Halodoc telemedicine application (rcount > rtable = 0.611> 0.197, = 0.05), 2. All indicators on the therapeutic communication variable media has an effect on patient satisfaction variables. The recommendation from this research is that the company should continue to pay attention to the aspects of doctor's communication skills so that all users have a good experience and satisfaction at the time of consultation. Keywords : Halodoc, Satisfaction, Therapeutic communication..